UJI MUTU FISIK SEDIAAN LIP BALM DAN KADAR TOTAL ANTOSIANIN EKSTRAK DAUN JATI (Tectonagrandislinn., F.) - Lindra Putri, Jessika Ukurmehuli; Hidayat, Rahmat; Wardani, Tatiana Siska (Universitas Imelda Medan, 2025)
Lip balm is a product that serves to prevent dryness of the lips by increasing moisture and protecting them from the adverse effects of the environment. In making this lip balm, Teak leaves (Tectonagrandislinn., F) are used as a natural colorant because they contain pigments, especially anthocyanins. Anthocyanins are flavonoid compounds that have antioxidant properties. This study aims to determine the total anthocyanin content in teak leaf extract and design a lip balm formulation that meets physical quality standards. In addition, the study also tested variations in concentration to find the best formulation. The type of research used with experimental methods involving physical quality tests of lip balm preparations and total anthocyanin levels of teak leaf extract.The results showed that lip balms with formula 0 (no extract), formula I (2% extract), formula II (3% extract), and formula III (4% extract) met the physical quality standards based on SNI 1-4399-1996, including in the aspects of homogeneity, adhesion, spreadability, viscosity, and pH. The total anthocyanin content in teak leaf extract was 68.298 mg/L. In addition, variations in extract concentration also affected the panelists' level of liking, where formula III with a concentration of 4% was the most preferred because it had an even composition, suitable pH, good spreadability and adhesiveness, and did not cause irritation.